2018
DOI: 10.1051/0004-6361/201832592
|View full text |Cite
|
Sign up to set email alerts
|

X-ray, UV, and optical observations of the accretion disk and boundary layer in the symbiotic star RT Crucis

Abstract: Compared to mass transfer in cataclysmic variables, the nature of accretion in symbiotic binaries in which red giants transfer material to white dwarfs (WDs) has been difficult to uncover.The accretion flows in a symbiotic binary are most clearly observable, however, when there is no quasi-steady shell burning on the WD to hide them. RT Cru is the prototype of such non-burning symbiotics, with its hard (δ-type) X-ray emission providing a view of its innermost accretion G. J. M. Luna et al.: RT Crucis; X-ray, U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…[2.2,2.3] using advective hot flows). For example, multi-satellite X-ray observations of RT Cru indicate that the BL is optically thin and stays thin throughout a brightening event where the rate of accretion is increased to 6.7×10 −9 M ⊙ yr −1 (Luna et al, 2018a) (e.g., typically seen in DNe state changes). This observation also indicates a Compton reflection hump E>10 keV as detected in accreting (XRB) systems.…”
Section: White Dwarf Symbioticsmentioning
confidence: 99%
“…[2.2,2.3] using advective hot flows). For example, multi-satellite X-ray observations of RT Cru indicate that the BL is optically thin and stays thin throughout a brightening event where the rate of accretion is increased to 6.7×10 −9 M ⊙ yr −1 (Luna et al, 2018a) (e.g., typically seen in DNe state changes). This observation also indicates a Compton reflection hump E>10 keV as detected in accreting (XRB) systems.…”
Section: White Dwarf Symbioticsmentioning
confidence: 99%
“…Although symbiotic stars mostly display soft or supersoft X-ray emission (see e.g. Muerset et al 1997), a few of them show hard X-ray emission, namely RT Cru (Luna & Sokoloski 2007;Kennea et al 2009;Eze 2014;Ducci et al 2016;Luna et al 2018), CH Cyg (Kennea et al 2009;Eze 2014), T CrB (Tueller et al 2005;Luna et al 2008;Kennea et al 2009;Eze 2014), CD-57 3057 (SS73 17) (Smith et al 2008;Kennea et al 2009;Eze et al 2010;Eze 2014), and MWC 560 (Stute & Sahai 2009). These hard X-ray emitting symbiotic systems pose a chal-⋆ E-mail: danehkar@umich.edu lenge to our understanding of accreting white dwarfs (WDs).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a high cooling flow temperature of kTmax = 51 +3 −2 keV was estimated from combined archival INTEGRAL γ-ray satellite and Swift/XRT data, in addition to kTmax = 79.9 +••• −19.9 keV from Suzaku data (Ducci et al 2016). More recently, Luna et al (2018) obtained a maximum post-shock temperature of kT = 53 ± 4 keV from spectral fitting analysis of Suzaku and NuSTAR+Swift observations, and suggested a WD mass of 1.25 ± 0.02M⊙. Previous X-ray observations of RT Cru have effectively measured its spectral features in the hard X-ray excess (≫ 1 keV), except for the recent Chandra observations in 2015 that we analyze here.…”
Section: Introductionmentioning
confidence: 99%
“…et.al. [4] showed that the RT Cru object is a prototype of symbiotics without burning the shell on a dwarf; its hard type of X-ray radiation gives an idea of its most internal accretion structures. Over the past 20 years, RT Cru has experienced two similar events of increasing brightness, separated by an interval of 4000 days and with an amplitude of ΔV = 1.5 mag.…”
mentioning
confidence: 99%
“…Spectral and temporal analysis of multiwave observations indicate that accretion continues through a disk that reaches the surface of a white dwarf. Moreover, the similarity of ultraviolet and x-ray fluxes indicate that the boundary layer of the accretion disk remained optically thin with respect to its own radiation during the increase in brightness when the accretion rate on WD increased to 6.7 × 10 -9 Mo / yr. [4] Among symbiotics, there are also white dwarfs with quasi-stable burning of the shell on their surface, although the origin of this burning is not yet clear. Probably in slow symbiotic, it is associated with past thermonuclear release.…”
mentioning
confidence: 99%